Correlation of Stature with Thickness of Tendo Achilles in Adult Bangladeshi - Amin, Sanjida; Ara, Shamim; Akter, Rahenur; Naznin, Rawshon; Marium, Umma; Amin, Fatema (Bangladesh Journal of Anatomy, 2016)
Context: The tendoachillesis a vital structure in the bipedalic system of human propulsion. It maintains the posterior morphological trail of the foot. The tendon plays an important role in reducing the energy cost of locomotion by storing energy elastically and releasing it at a subsequent point in the gait cycle and based on that it forms the elastic component of the triceps surae musculotendinous unit. So measurement of tendon and detection of size is an important tool for assessment of tendon. The aim of the study was to correlate thickness, of tendo achilles with stature in several age groups of sedentary people as measured by ultrasonography. All the measurement of tendo achilles vary with different factors such as age, sex, stature, physical activities, dominance of ankle, race and ethnicity. Materials and Methods: This is a cross sectional analytical type of study conducted in the Department of Anatomy Dhaka Medical College from July 2013 to June 2014.The present study was performed on 200 tendo achilles of 100 people (Among them 50 were male and 50 were female). They were randomly selected from the patients who came to the Radiology Department of Dhaka Medical College Hospital for ultrasonography of any regions of their body other than leg. Result: In this study thickness of tendo achilles was measured in both legs of adult people and correlated with stature. Highly significant correlation was found between the thickness, of tendo achilles with stature (p<0.001). Conclusion: The information obtained from the present study may provide a better understanding of the morphologic characteristic of normal tendoachilles, which may help physiotherapists, radiologists, sports professionals, ortho-surgeons in making a more accurate diagnosis. Bangladesh Journal of Anatomy July 2016, Vol. 14, No. 2, pp. 32-35